2014
DOI: 10.1186/1743-8977-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent titanium dioxide nanoparticle deposition by intratracheal instillation and whole body inhalation: the effect of dose rate on acute respiratory tract inflammation

Abstract: BackgroundThe increased production of nanomaterials has caused a corresponding increase in concern about human exposures in consumer and occupational settings. Studies in rodents have evaluated dose–response relationships following respiratory tract (RT) delivery of nanoparticles (NPs) in order to identify potential hazards. However, these studies often use bolus methods that deliver NPs at high dose rates that do not reflect real world exposures and do not measure the actual deposited dose of NPs. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 77 publications
(87 reference statements)
5
95
0
1
Order By: Relevance
“…According to the measured tissue Ti levels, most of the amount applied remained in the lungs but the load measured in the brain and other organ samples was also considerably higher than in the rats without nano-TiO 2 exposure. The high degree of deposition of TiO 2 NPs in the lungs was in similar to the observation in 7 that a single amount instilled in the trachea of rats was completely retained in the lungs for 7 days.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to the measured tissue Ti levels, most of the amount applied remained in the lungs but the load measured in the brain and other organ samples was also considerably higher than in the rats without nano-TiO 2 exposure. The high degree of deposition of TiO 2 NPs in the lungs was in similar to the observation in 7 that a single amount instilled in the trachea of rats was completely retained in the lungs for 7 days.…”
Section: Discussionsupporting
confidence: 86%
“…In some experiments, access of TiO 2 NPs to the rat brain after application to the airways was verified, together with damage to the blood-brain barrier 6 ; the same authors also reported dose-and time-dependent toxicity of the identical TiO 2 NPs on rat astrocytes in vitro. Others, however, found that most of the nano-TiO 2 remained in the lungs 7 . Functional alterations, possibly resulting from access of TiO 2 NPs to the brain, have been described at the level of electrophysiological changes only a few times up to now.…”
mentioning
confidence: 96%
“…8). Figure 8B shows there is less than 5% variability between pipette volumes within a pipette step over all rounds performed no effect in the lungs of the rats (Baisch et al, 2014). Further studies may be required to clarify which physiologically relevant parameters of an in vivo system are captured in actual in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have had a significant impact in vitro (DeLoid et al, 2015(DeLoid et al, , 2017Pal et al, 2015;Watson et al, 2016). More recent comparative work has shown that IT dose rate and mode of administration impact considerably the study outcomes (Baisch et al, 2014;Silva et al, 2014). What effects did such dispersions have during their subsequent use in IT and IV applications?…”
Section: Commentarymentioning
confidence: 99%